การปรับปรุงประสิทธิผลโดยรวมในกระบวนการห่อไม้ฝา - Ratanawilai, Thanate; Srisuk, Vuttikrai (Naresuan University Journal: Science and Technology (NUJST), 2015)
การศึกษากระบวนการห่อมัดไม้ฝาของโรงงานกรณีศึกษาครอบคลุมขั้นตอนตั้งแต่การเบิกไม้ฝาที่ผ่านการพ่นสีแล้วมาห่อฟิล์มแยกเป็นห่อละ 5 แผ่นให้ความร้อนกับฟิล์มเป่าให้ฟิล์มเย็นตัวและมัดรวมเป็นมัดๆ ละ 420 แผ่นและนำไปกองเก็บเพื่อส่งมอบให้พัสดุสินค้า โดยใช้พนักงาน 2 คนต่อกะ สำหรับเดินเครื่องและตรวจสอบคุณภาพห่อมัดและจะใช้พนักงานรับเหมาอีก 15 คนช่วยในการขนย้าย การศึกษาเริ่มจากขั้นตอนในการห่อมัดไม้ฝา จัดเก็บรวบรวมข้อมูล วิเคราะห์ เพื่อหาสาเหตุของปัญหา จัดทำแผนการแก้ไข ดำเนินการแก้ไขปัญหาตามแผน สรุปผลการทดลอง ตรวจสอบผลแล้วจัดทำมาตรฐาน ผลการศึกษากระบวนการ ค้นหาข้อบกพร่องของเครื่องจักรและดำเนินการแก้ไขพบว่า หลังการปรับปรุงประสิทธิผลโดยรวมของเครื่องจักรอุปกรณ์ เพิ่มขึ้น 12.5% (จาก 55.8% เพิ่มเป็น 68.3%) ประสิทธิภาพโดยรวมของเครื่องจักรอุปกรณ์ เพิ่มขึ้น 32.5% (จาก 35.7% เพิ่มเป็น 68.3%) และอัตราการผลิตเพิ่มขึ้น 0.98 ตันต่อชั่วโมง เพิ่มขึ้น 22.68% (เดิม 4.32 ตันต่อชั่วโมง เพิ่มเป็น 5.30 ตันต่อชั่วโมง) โดยสูงกว่าเป้าหมายซึ่งกำหนด 10 % ทั้งสามตัวชี้วัด ต้นทุนการผลิตลดลง 36 บาทต่อตัน สำหรับงวดระยะเวลาคืนทุน 0.40 เดือน คุ้มค่าต่อการลงทุน ซึ่งผลการปรับปรุงบรรลุตามวัตถุประสงค์ที่กำหนด คำสำคัญ :  ประสิทธิผลโดยรวมของเครื่องจักร กระบวนการห่อไม้ฝา ประสิทธิภาพโดยรวมของเครื่องจักร            This study focuses on the packaging process of wood plank packs including the process of colored wood planks requisition, wrapping 5 wood planks with film, and   heating them up. The heated planks were blown with cool air to decrease the temperature. Afterwards, 420 wood planks were packed into one stack and ready for delivery. Two employees were used for machine operation and inspection of wood plank packs. Loading and unloading of wood plank packs were done by 15 contractor employees. This research includes the study of wood planks wrapping process, data collection, analyze the data, create the plans to solve the problems, implement the plans, conclude the results, then verify the results, and finally create the standard procedures. After studying the current process, searching for any defects of the machines, and implementation of the purposed solution, the result showed that the OEE value increased 12.5% (from 55.8% to 68.3%), while TEEP value increased 32.5% (from 35.7% to 68.3%). The production rate increased 22.68%, 0.98 tons per hour (from 4.32 tons per hour to 5.30 tons per hour) resulting in the production costs decreased 36 baht per ton. The increasing of 3 indicators is higher than that of the target value at 10%. The payback period 0.40 month was profitable investment. The results of improvement were shown to achieve the target of this research. Keywords : overall equipment effectiveness, wood plank packaging process, total effective equipment performance
Keywords: ประสิทธิผลโดยรวมของเครื่องจักร กระบวนการห่อไม้ฝา ประสิทธิภาพโดยรวมของเครื่องจักร overall equipment effectiveness, wood plank packaging process, total effective equipment performance